2018
DOI: 10.1038/s41467-017-02798-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional decomposition reveals active chromatin architectures and cell specific regulatory interactions

Abstract: Transcriptional regulation is tightly coupled with chromosomal positioning and three-dimensional chromatin architecture. However, it is unclear what proportion of transcriptional activity is reflecting such organisation, how much can be informed by RNA expression alone and how this impacts disease. Here, we develop a computational transcriptional decomposition approach separating the proportion of expression associated with genome organisation from independent effects not directly related to genomic positionin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 72 publications
8
62
0
Order By: Relevance
“…We propose that this applies across active loci and explains fine-scale Acompartments and enhancer-gene communication both within and across TADs. Evidence supporting MLL/Trithorax complexes, associated histone modifications, and transcription factors as mediators of such phase transition is now emerging (Bonev et al, 2017;Weintraub et al, 2017;Yan et al, 2018;Huang et al, 2018;Rennie et al, 2018). Importantly, rather than being necessary for the establishment of these active compartments and the interactions therein, cohesin might either play a secondary role or even act to oppose them (Rao et al, 2017;Schwarzer et al, 2017).…”
Section: Transcription As a Looping Forcementioning
confidence: 99%
See 1 more Smart Citation
“…We propose that this applies across active loci and explains fine-scale Acompartments and enhancer-gene communication both within and across TADs. Evidence supporting MLL/Trithorax complexes, associated histone modifications, and transcription factors as mediators of such phase transition is now emerging (Bonev et al, 2017;Weintraub et al, 2017;Yan et al, 2018;Huang et al, 2018;Rennie et al, 2018). Importantly, rather than being necessary for the establishment of these active compartments and the interactions therein, cohesin might either play a secondary role or even act to oppose them (Rao et al, 2017;Schwarzer et al, 2017).…”
Section: Transcription As a Looping Forcementioning
confidence: 99%
“…Equally, domain boundaries might not directly involve bound RNA polymerase or transcriptional activity, but rather arise due to spatial segregation between active and inactive chromatin compartments (Rowley et al, 2017). Nevertheless, the close relationship between transcription and chromatin architecture is well illustrated in studies where transcriptional data sufficed for correctly predicting 3D genome folding (Rowley et al, 2017;Rennie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional shape of chromosomes has significant influence in many critical cellular processes, including gene expression and regulation [7,14,26], replication timing [24,2], and overall nuclear organization [10]. The wide range of processes related to chromosome structure suggests that understanding this component is crucial to a broader explanation of many genomic mechanisms, yet it remains a challenge to study this complex system.…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of the first genome-wide expression experiments, it became clear that expression levels were related to the organization of genes in linear dimension (1). More recent studies have shown that transcriptional activation may spread in "waves" that affect nearby genes (2) and that a significant proportion of gene expression events may be attributed to genomic position (3). Such tendencies are reflected on evolutionary constraints, with genes in close proximity showing similar patterns of evolution (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…They often overlap with characteristic epigenetic modification patterns (10,11), different combinations of which have been shown to delineate epigenetic "chromatin states" that reflect different levels of regulatory and transcriptional activity (12)(13)(14). Overall, there is an increasing interest in the concept of genome compartmentalization focusing on its underlying regulatory and transcriptional activity, evident in recent approaches on cisregulatory domains (15) and in attempts to model gene expression levels on the basis of genomic position (3). The biomedical importance of this organization is particularly important in various types of cancer, where extensive genomic translocations are the main cause for aberrant regulation of genes and eventually for pathogenesis (16).…”
Section: Introductionmentioning
confidence: 99%